EFFECT OF HUSBAND’S SUPPORT DURING SECOND STAGE DURATION OF LABOR IN PRIMIGRAVIDA CHILDBIRTH - Dwi Rahayu, Ayu Ngurah (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE Anxiety and fear is usually felt by primigravida women who have not had experience giving birth . Anxiety could increase catecholamines level which potentially lead to prolonged labor. Husband’s support during labor is able to affect the oxytocin hormones in increasing uterine contractions and shortening the second stage duration. This study aims to determine the effect of husband’s support during second stage duration of labor in primigravida women who deliver their baby in RSUD Badung. The research type is Pre-experimental Design study with One-Shot Case Study design form. The samples of this study were 16 people who obtained from nonprobability consecutive sampling sample technique. The average value of second stage duration and intervention of husband’s support actively obtained for 26.10 minutes. The data analysis using One Sample T-test obtained p = 0.000 (??0.05) as a result Ha is accepted, which means husband’s support give a stimulus to primigravida women’s in second stage duration of labor. The result of this study could be a reference in labor by enhancing the role of the husband in supporting women in labor. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Husband’s Support, Second Stage, Primigravida